Roedores en la dieta de dos aves rapaces nocturnas (Bubo virginianus y Tyto alba) en el noreste de Durango, México - Aragón, Elizabeth E; Castillo, Benjamín; Garza, Alfredo (Instituto de Ecología, A.C., 2002)
We studied the diet of two species of owls, and assessed the rodents communities and their relative densities from March 1996 through February 1997 in the Mapimí Biosphere Reserve, Durango, México: Great Horned Owl (Bubo virginianus) and Barn Owl (Tyto alba). The objectives were to understand the predator-prey relationships by comparing the availability and use of rodents by these owls. We analyzed 146 regurgitated pellets of five Great Horned Owl and 63 of four Barn Owl, both of seven samples. This species had different prey items: Great horned owls consumed eleven rodents species, while Barn owls consumed only six. In both bird’s diets, arthropods and shrews were detected, and Great Horned Owl furthermore consumed ferns and reptiles. Based on the availability of rodents, the Great Horned Owl preferred eight rodent species: Silky Pocket Mouse, White- hroated Woodrat, Western harvest mouse, Merriam's Kangaroo Rat, Desert Pocket Mouse, Nelson's Kangaroo Rat, Nelson's Pocket Mouse and Cactus Mouse. Barn Owl preferred five prey species: Silky Pocket Mouse, Desert Pocket Mouse, Nelson's Kangaroo Rat, Merriam's Kangaroo Rat and Cactus Mouse. Diets of the two raptors have little overlap, except during reproduction and chick rearing. Food habits of these birds appear to be dependent upon the foraging habitat: Great Horned Owls foraged in creosote bush, prickly pear scrub and grasslands, whereas the Barn Owl foraged only in the grassland. Prey selection depended on the density, biomass (White-throated Woodrat, Merriam's Kangaroo Rat and Nelson's Kangaroo Rat) and perhaps easy capture of the rodents (P. flavus). GreatHorned owls was a generalist and opportunist, while the Barn Owl was a generalist with respect to prey selectivity.